Epidemiological Survey of Cutaneous Leishmaniasis in Hamadan Province (2002-2007) - Amirhosein Zahirnia; Alireza Moradi; Noruz Ali Norozi; Seyyed Jalalodin Nader Bathaii; Hosein Erfani; Abbas Moradi (پزشکی بالینی ابن سینا, 2009)
Introduction & Objective: Cutaneous leishmaniasis as one of the most important tropical diseases, is endemic in different parts of Iran. World Health Organization (WHO) has recommended and supported the investigation on this zoonotic disease. The purpose of this descriptive study was to determination some epidemiological aspects of cutaneous leishmaniasis in Hamadan Province. Materials & Methods: All confirmed and recorded cutaneous leishmaniasis cases who were diagnosed during 2002-2007 in Hamadan province entered in our study and their demographic and epidemiological information was analyzed by SPSS software. Results: According to the results of this study, from a total of 210 cases of cutaneous leishmaniasis, 197 (93.8%) were male and 13 (6.2%) were female. The mean incidence of cutaneous leishmaniasis was 2.05/100000. The most common age group was 15-24 and 85.7% of the patients were between 15 to 44 years old. 99% of the patients had a history of stay in or trip to an endemic area. Conclusion: Migration of susceptible populations especially men in labor ages (>15 years old) to endemic areas, whose exposure to infection is highly probable, is the main cause of cutaneous leishmaiasis disease in Hamadan province. This situation indicates that cutaneous leishmaniasis is not endemic in Hamadan province.